2008
DOI: 10.1517/17530059.2.5.511
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in carcinoma of the gallbladder

Abstract: The list of the biomarkers that has been evaluated is exhaustive. Important ones are CA 242, CA 19-9, CA 15-3, CA 125, CA 50, CA 72-4, CEA, mucins, PCNA, RCAS1 and arginase. Important genetic and molecular ones are overexpression of p53, loss of heterozygosity (LOH) at chromosome 17p, LOH at chromosome 9p and 8q, mutations in the K-ras gene, LOH of chromosome 18, and FHIT gene mutation. Of these, CA 19-9 holds maximum promise. However, it has low specificity. Other more extensively studied markers are p53, bcl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“…It might have particular clinical relevance for differential hepatobiliary cancer detection and should be followed up by a large multi‐centre study. A current alternative serum biomarker for biliary cancer diagnosis as proposed by the ESMO Clinical Practice Guidelines is CA 19‐9 29 but it is associated with low sensitivity and specificity of 62% and 63%, respectively, 32,48 and is not suitable to discriminate between cancer entities. Several serum biomarkers and metabolites have been identified as potential candidates for minimal invasive discrimination of HCC and intrahepatic CCA 10,49 but until now no liquid biopsy marker achieving a better clinically useful performance exists underlining the relevance of our study in terms of hepatobiliary cancer management.…”
Section: Discussionmentioning
confidence: 99%
“…It might have particular clinical relevance for differential hepatobiliary cancer detection and should be followed up by a large multi‐centre study. A current alternative serum biomarker for biliary cancer diagnosis as proposed by the ESMO Clinical Practice Guidelines is CA 19‐9 29 but it is associated with low sensitivity and specificity of 62% and 63%, respectively, 32,48 and is not suitable to discriminate between cancer entities. Several serum biomarkers and metabolites have been identified as potential candidates for minimal invasive discrimination of HCC and intrahepatic CCA 10,49 but until now no liquid biopsy marker achieving a better clinically useful performance exists underlining the relevance of our study in terms of hepatobiliary cancer management.…”
Section: Discussionmentioning
confidence: 99%
“…RCAS1 is important in tumor progression or metastasis. Recent studies showed RCAS1 was expressed in various cancers . RCAS1 expression also has been associated with poor differentiation and advanced stage .…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that RCAS1 on tumor cells may convey an important advantage in avoiding host immune surveillance. RCAS1 is expressed in various cancers including those of the lung, esophagus, breast, liver, pancreas, stomach and gallbladder . RCAS1 expression has also been associated with aggressive tumor phenotypes, such as poor differentiation and advanced stage .…”
Section: Discussionmentioning
confidence: 99%